Adaptive Brain Shut-Down Counteracts Neuroinflammation in the Near-Term Ovine Fetus - Xu, Alex; Durosier, Lucien Daniel; Ross, Michael G.; Hammond, Robert; Richardson, Bryan S.; Frasch, Martin G. (Frontiers in Neurology, 2014)
Objective: Repetitive umbilical cord occlusions (UCOs) in ovine fetus leading to severe acidemia result in adaptive shut-down of electrocortical activity (ECOG) as well as systemic and brain inflammation. We hypothesized that the fetuses with earlier ECOG shut-down as a neuroprotective mechanism in response to repetitive UCOs will show less brain inflammation and, moreover, that chronic hypoxia will impact this relationship. Methods: Near term fetal sheep were chronically instrumented with ECOG leads, vascular catheters and a cord occluder and then underwent repetitive UCOs for up to 4 hours or until fetal arterial pH was < 7.00. Eight animals, hypoxic prior to the UCOs (SaO2< 55%), were allowed to recover 24 hours post insult, while 14 animals, five of whom also were chronically hypoxic, were allowed to recover 48 hours post insult, after which brains were perfusion-fixed. Time of ECOG shut-down and corresponding pH were noted, as well as time to then reach pH<7.00 (ΔT). Microglia (MG) were counted as a measure of inflammation in grey matter layers 4-6 (GM4-6) where most ECOG activity is generated. Results are reported as mean±SEM for p<0.05. Results: Repetitive UCOs resulted in worsening acidosis over 3 to 4 hours with arterial pH decreasing to 6.97±0.02 all UCO groups’ animals, recovering to baseline by 24 hours. ECOG shut-down occurred 52±7 min before reaching pH < 7.00 at pH 7.23±0.02 across the animal groups. MG counts were inversely correlated to ΔT in 24 hours recovery animals (R=-0.84), as expected. This was not the case in normoxic 48 hours recovery animals, and, surprisingly, in hypoxic 48 hours recovery animals this relationship was reversed (R=0.90). Conclusion: Adaptive brain shut-down during labour-like worsening acidemia counteracts neuroinflammation in a hypoxia- and time-dependent manner.